Does Cultural Pluralism Matter? Views from Experts Involved in the Production of Accounting Textbooks - Irsyadillah Irsyadillah; Raihani Raihani; Zulfadhli Zulfadhli; Alhashmi Aboubaker Lasyoud (Universitas Syiah Kuala, 2023)
Objective –The paper seeks to evaluate the perceptions and attitudes of individuals involved in the production of accounting textbooks about providing cultural pluralism in the textbooks.Methodology –This paper used semi-structured interviews with key actors of accounting textbook production, including translators, independent reviewers, adaptors, authors and commissioning editors. With one exception, all interviewees are also academics at universities. Results –The paper finds that accounting textbooks are cultural and political artifacts that reflect the the cultural, political, and ideological viewpoints of the powerful groups in the world. In other words, the textbook contents are the results of power domination. They have used accounting textbooks as powerful educational media to homogenise cultural and ethical values of accounting and accounting education to be solely based on Anglo-American capitalism. This has greatly affected the professionals involved in the textbook production. Therefore, it is not an urgent matter for them to incorporate diversity of perspectives into accounting textbooks used in Indonesia.Novelty/Originality –Although accounting research has explored the issues of accounting textbooks, such as the readability, price, selection, and use, studies that consider the political and cultural role of accounting textbooks especially from the perspective of individual involved in the textbook production are still scant. In particular, there is no research in Indonesia that presents the views of people who produce accounting textbooks regarding the content of their textbooks.